Analysis of the potential solid waste palm oil as animal feed cattle in province Riau - Cattelya Flordeluna; Nursiah Chalid; Mardiana ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to identify and analyze the potential of solid waste as cattle feed in the Riau province where oil palm solid waste is estimated each year has increased the amount of solid waste production as the increasing production of fresh fruit bunches ( FFB ) is in if every year .The data used in this study are primary and secondary data . The method used in this peneilitan is descriptive method . To see the right strategy in the potential of oil palm solid waste as cattle feed in the province of Riau , then used the method of SWOT analysis .With the potential approximity Solid waste can be seen in the amount of solid waste production from year 2006 - 2011 continues to increase . This is due to increase the amount of FFB ( fresh fruit bunches ) are processed each year . Based on the results of the SWOT analysis can be seen in the analysis of potential strategies palm solid waste as cattle feed in Riau Province namely WO strategy . WO strategy is a strategy to survive by reducing weaknesses and avoid threats , namely The company delivers directly to the location of the solid waste breeders , giving Solid waste must be mixed with other feed ingredients that exist around the location so that the cows are not malnourished , and the government provides assistance cow the farmer groups that use Solid waste to developing cattle population and to increase the income of farmers .Keywords : palm oil , potential , solid waste